Metodología de selección de comunidades para la implementación de miniredes como alternativa de electrificación rural en zonas no interconectadas de la región del putumayo, colombia (2021)
The document presents a methodology for selecting communities for the implementation of generation systems through minigrids (solar, diesel, hybrid) to electrify rural territories isolated from the electrical network. The Putumayo Department, Colombia, is taken as the study site, which has a low rate of rural electrification, mainly due to the difficult geographical conditions that the region has to extend local distribution grids. In the first instance, the communities will be classified according to certain pre-established parameters. As an example of a study, the three best ranked sites will be chosen to implement this type of technology. Using HOMER software, the technical and operational performance of the three isolated mini-grid configurations will be evaluated: diesel, solar and hybrid. In the same way, an economic study will be carried out, the Net Present Cost and the Levelized Cost of Energy are calculated and compared for each proposed case. Finally, it is concluded about the results obtained and the convenience of installing these systems in small remote communities.